Transformasi dari Politik Jarak Jauh ke Politik Identitas di Gerakan Surah Buku Yogyakarta - Muhyi Atsarissalaf (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
This article discusses the transformation of the Aceh diaspora political movement in Yogyakarta. By taking the community of Gerakan Surah Buku, this article strengthens Missbach's (2012) argument that the long-distance politics of the Acehnese diaspora has shifted to identity politics, meaning that the long-distance politics of the diaspora has not completely disappeared, but has undergone changes. The position of this article then tries to show these changes through ethnographic research in one of the literacy communities, Gerakan Surah Buku, Yogyakarta. This article shows that the form of identity politics is not only the effect of the shift of long-distance politics, but has become an alternative and creative articulation of the remnants of the previous Acehnese diaspora long-distance political movement. This research uses auto-ethnography, a research method that allows researchers to be directly involved for a long period of time. The article also shows how ethnic identities that are struggling in the diaspora have formed a hybrid culture in articulating trending issues in youth activism movements, such as human rights, peace, justice and freedom.